Magnesia doped Ag/Al2O3 - sulfur tolerant catalyst for low temperature HC-SCR of NOx - More, Pavan M.; Jagtap, Neelam; Kulal, Atul B.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2014)
A series of magnesia doped Ag/Al2O3 catalysts were prepared by modified impregnation method using boehmite as alumina precursor. The prepared catalysts were characterized and tested for the SCR of NOx using propene as reductant under lean condition. Doping of magnesia improved the low temperature catalytic activity for HC-SCR of NOx as well as sulfur tolerance. Maximum 98% NO conversion with 100% selectivity for N-2 was obtained at 350 degrees C with 7% Mg doping to Ag/Al2O3. The improvement in low temperature activity and the sulfur tolerance has been correlated to decreased acidity after addition of magnesia to alumina support. In situ FTIR study showed that the deactivation in the presence of SO2 was due to the sulfation of silver and aluminum sites in Ag/Al2O3 catalyst, however its formation was suppressed in case of magnesia doped Ag/Al2O3 improving its sulfur tolerance. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: HC-SCR; Low temperature activity; NOx; Sulfur tolerance

Mesoporous tin oxide: an efficient catalyst with versatile applications in acid and oxidation catalysis - Manjunathan, Pandian; Marakatti, Vijaykumar S.; Chandra, Prakash; Kulal, Atul B.; Umbarkar, Shubhangi B.; Ravishankar, Raman; Shanbhag, Ganapati V. (Catalysis Today, 2018)
Mesoporous tin oxide was prepared by template assisted and template-free methods. As-prepared materials were calcined at various temperatures to generate different nature (Bronsted and Lewis), amount and strength of acidic sites. The physico-chemical properties of the catalysts were studied by XRD, N-2 sorption, pyridine-FTIR, NH3-TPD, DRS UV-vis, TGA, SEM, TEM, H-1 MAS and Sn-119 MAS NMR analyses. The catalytic behavior of mesoporous tin oxide catalysts was evaluated for acetalization and ketalization of glycerol with benzaldehyde and acetone respectively under solvent free conditions. The catalytic performance of mesoporous tin oxide was compared with that of other conventional solid acid catalysts namely H-ZSM-5, H-mordenite, H-beta, Al-MCM-41, Al-SBA-15 and Al-TUD-1. The efficiency of mesoporous tin oxide was also tested for cyclohexene epoxidation reaction. The catalyst prepared by template assisted method showed excellent catalytic performance compared to other catalysts due the difference in nature and amount of acidic sites in the catalyst. Meso-SnO2-T-350 was stable and reusable catalyst for four cycles without any appreciable loss in activity, and therefore it offers a good catalyst for potentially wide applications.